3-D Thermomechanical Tire–Pavement Interaction Model for Evaluation of Pavement Skid Resistance. Issue 3 (March 2021) - Anupam, K.; Tang, T.; Kasbergen, C.; Scarpas, A.; Erkens, S.
Skid resistance is known to be affected by environmental conditions such as ambient temperature and pavement temperature. Finite element (FE) modeling has been an effective and efficient way to study the effects of temperature on skid resistance. However, existing FE models either are not able to incorporate the pavement surface characteristics or only perform heat transfer analysis per the two-dimensional (2-D) cross-section of the tire, which could lead to inaccurate predictions of skid resistance. Therefore, the aim of the current study was to develop a three-dimensional, coupled thermomechanical tire–pavement interaction model to investigate the variations in skid resistance as a function of ambient temperature and pavement temperature. The advantages and capability of the proposed model were highlighted by comparing the tire temperature profiles predicted by the proposed model and by the existing 2-D staggered model. Parametric studies of various factors that affect skid resistance were carried out. On the basis of the output results, a relationship between skid resistance and different parameters is proposed.